2018
DOI: 10.1177/1367493518804097
|View full text |Cite
|
Sign up to set email alerts
|

Coping with the unfamiliar: How do children cope with hospitalization in relation to acute and/or critical illness? A qualitative metasynthesis

Abstract: The aim of this study was to identify and describe how young children cope with hospitalization in relation to acute and/or critical illness. The study is a qualitative metasynthesis inspired by the approach described by Sandelowski and Barroso. Based on an exhaustive literature search, six studies were included. Data were analyzed through a taxonomic analysis. The findings revealed that the hospitalized children face a variety of challenges during admission to the hospital due to acute and/or critical illness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 40 publications
0
18
0
7
Order By: Relevance
“…61 Furthermore, previous literature emphasised the significance of paediatric healthcare professionals who promote play, 3 62 but there is a lack of formal interprofessional training programmes available. 63 64 Our review shows that treatment and care by various healthcare professionals may benefit from the incorporation of play interventions. This necessitates high-quality research evaluating the short, sustained and long-term effects of play interventions in hospitals to help overcome current barriers, such as lack of training among clinical staff.…”
Section: Discussionmentioning
confidence: 99%
“…61 Furthermore, previous literature emphasised the significance of paediatric healthcare professionals who promote play, 3 62 but there is a lack of formal interprofessional training programmes available. 63 64 Our review shows that treatment and care by various healthcare professionals may benefit from the incorporation of play interventions. This necessitates high-quality research evaluating the short, sustained and long-term effects of play interventions in hospitals to help overcome current barriers, such as lack of training among clinical staff.…”
Section: Discussionmentioning
confidence: 99%
“…Advances in paediatric health care have generated a shift in focus from a professional and family-centric one to a childcentric one, supporting the inclusion of children as active partners in their own health care. In spite of this change, most children still desire to be more involved in health care than they are allowed to (Coyne & Kirwan, 2012;Gilljam, Arvidsson, Nygren, & Svedberg, 2016;Sjöberg, Amhliden, Nygren, Arvidsson, & Svedberg, 2015) and this contributes to hospitalised children often feeling uncertain about what is happening to them, and experiencing loss of control (Jepsen, Haahr, Eg, & Jørgensen, 2018). There is a large body of evidence demonstrating a reduction in fear, increased self-esteem and better preparation for unpleasant treatments if children are involved in their health care (Kelly, Mowbray, Pyke-Grimm, & Hinds, 2017;Vis, Strandbu, Holtan, & Thomas, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of having a parent as interpreter is also highlighted by Bray et al (2019) as children are reliant on their parents for access to information. In absence of a parent, Jepsen et al’s (2019) finding emphasises that this important gap is often filled by healthcare professionals.…”
mentioning
confidence: 99%
“…Jepsen and colleagues (2019) found that hospitalised children face a variety of challenges during admission to the hospital due to acute and/or critical illness. A pressing challenge, which surely would have also faced children admitted to Coram’s Foundling Hospital, was that of coping with ‘the unfamiliar’.…”
mentioning
confidence: 99%
See 1 more Smart Citation